Religious experience and the knowledge of God : the evidential force of divine encounters - Netland, Harold A., 1955- (Grand Rapids, MI. Baker Academic, 2022)
'For many Christians, personal experiences of God provide an important ground or justification for accepting the truth of the gospel. But we are sometimes mistaken about our experiences, and followers of other religions also provide impressive testimonies to support their religious beliefs. Religious Experience and the Knowledge of God offers an introduction to the complex topic of religious experience and its viability as support for Christian belief, lending credibility to the Christian claim that experiences support our beliefs and actions. Harold Netland explores from a philosophical and theological perspective the viability of divine encounters as support for belief in God, arguing that some religious experiences can be accepted as genuine experiences of God and can provide evidence for Christian beliefs. The book also draws out the implications of religious experience for Christian witness, missiology, and apologetics in today's globalizing and religiously diverse world'--
Introduction -- Religious experience : mapping the conceptual territory -- Religious experience and interpretation -- The critical-trust approach -- Edwards and Wesley on experiencing god -- Experiencing god, basic beliefs, and the holy Spirit -- Mysticism -- Theistic experiences and religious diversity -- Conclusion.
Includes bibliographical references (pages 263-282) and index.
Keywords: Edwards, Jonathan, -- 1703-1758.; Wesley, John, -- 1703-1791.; Christianity -- Psychology; Experience (Religion); God (Christianity) -- Knowableness